Pterosin B prevents chondrocyte hypertrophy and osteoarthritis in mice by inhibiting Sik3 - Yahara, Yasuhito; Takemori, Hiroshi; Okada, Minoru; Kosai, Azuma; Yamashita, Akihiro; Kobayashi, Tomohito; Fujita, Kaori; Itoh, Yumi; Nakamura, Masahiro; Fuchino, Hiroyuki; Kawahara, Nobuo; Fukui, Naoshi; et al. (Nature communications, 2016)
Osteoarthritis is a common debilitating joint disorder. Risk factors for osteoarthritis include age, which is associated with thinning of articular cartilage. Here we generate chondrocyte-specific salt-inducible kinase 3 (Sik3) conditional knockout mice that are resistant to osteoarthritis with thickened articular cartilage owing to a larger chondrocyte population. We also identify an edible Pteridium aquilinum compound, pterosin B, as a Sik3 pathway inhibitor. We show that either Sik3 deletion or intraarticular injection of mice with pterosin B inhibits chondrocyte hypertrophy and protects cartilage from osteoarthritis. Collectively, our results suggest Sik3 regulates the homeostasis of articular cartilage and is a target for the treatment of osteoarthritis, with pterosin B as a candidate therapeutic. Therapies are needed for the prevention of chondrocyte hypertrophy and thinning of articular cartilage, features of osteoarthritic joint destruction. Here, the authors show that interfering with Sik3 signalling can increase the size of the chondrocyte population and reduce severity of a surgically induced mouse model of osteoarthritis.